Environmental catlysis over gold-based materials - Avgouropoulos, George; Tabakova, Tatyana (Cambridge : RSC Publishing, 2013)
This book presents the major developments in hydrogen-related catalytic and electrocatalytic reactions over gold-based materials over the last decade, including many of the advances made by academic and industrial researchers. Gold-based catalysts with potentially exciting new applications in hydrogen technology (e.g. purification of hydrogen, anode/cathode electrodes) are being investigated at a much higher rate than even before. A variety of techniques to synthesize, characterize and evaluate these materials is being employed. The book will be of interest to all those working in catalysis/green chemistry, in particular, to advanced level researchers in catalysis using gold-based materials. It is hoped that specialists in one reaction will read with interest the chapters on the neighbouring expertise. The book is also meant for PhD-students and advanced students interested in this area.
Bibliografija na koncu poglavij.
Kazalo.
Keywords: Catalysis; Transition metal catalysts; Gold; Environmental chemistry; fizikalna kemija -- kataliza -- katalizatorji -- nanodelci zlata -- sinteze -- fizikokemijske lastnosti -- reaktivnost zlata -- ogljikov monoksid -- preferencna kataliza -- kovinski karbidi -- HDS reacije -- reakcije hidrogeniranja -- aplikacije -- zborniki